2008
DOI: 10.1016/j.molimm.2007.07.034
|View full text |Cite
|
Sign up to set email alerts
|

IgM-mediated signaling is required for the development of a normal B cell memory response

Abstract: Mature B cells co-express both IgM and IgD types of antigen receptors before activation. Our earlier work has shown that the co-expression of IgD and IgM plays an important role in regulating the composition of antibody repertoire during a primary immune response. However, the roles of these two B cell receptors in the development of B cell memory responses remain unclear. The present study shows that during the secondary immune response to (4-hydroxy-3-nitrophenyl)acetyl (NP), IgM -/-mice secreted significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…However, IgM-deficient mice had reduced IgD + CD5 + B-1a population in the peritoneal cavity (Lutz et al, 1998), which is typically observed in mice with reduced BCR signaling, indicating that IgD alone cannot generate a signal that is as strong as that in WT B cells. Consistently, IgM-deficient mice showed reduced or delayed Ab production against a T-D Ag and in response to virus infection (Guo, Zhang, Zheng, & Han, 2008;Han et al, 2004;Lutz et al, 1998). More importantly, the finding that IgD is able to function when IgM is absent does not necessarily mean that IgD has the same function when IgM is present.…”
Section: Discussionmentioning
confidence: 89%
“…However, IgM-deficient mice had reduced IgD + CD5 + B-1a population in the peritoneal cavity (Lutz et al, 1998), which is typically observed in mice with reduced BCR signaling, indicating that IgD alone cannot generate a signal that is as strong as that in WT B cells. Consistently, IgM-deficient mice showed reduced or delayed Ab production against a T-D Ag and in response to virus infection (Guo, Zhang, Zheng, & Han, 2008;Han et al, 2004;Lutz et al, 1998). More importantly, the finding that IgD is able to function when IgM is absent does not necessarily mean that IgD has the same function when IgM is present.…”
Section: Discussionmentioning
confidence: 89%
“…We have become intrigued by the possibility that these various DBL domains may interact directly with lgM + B cells through the B cell receptor (BCR), as Cμ4 specific mAbs that inhibit PfEMP1 binding to IgM have also been shown to augment S phase entry of human B cells via the lgM + BCR (16,49). IgM-mediated signaling is required for the development of a normal B-cell memory response (50). Our finding that malaria parasites, known to promote polyclonal B-cell activation, encode molecules specific for Cμ4 certainly suggests that binding to this region of the BCR might also be immunologically important and merits further investigation.…”
Section: Interference With the Bcrmentioning
confidence: 99%